2018
DOI: 10.1111/apa.14375
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term study showed that vaccination protected paediatric renal transplant recipients from life‐threatening varicella zoster virus

Abstract: AimRenal transplant patients are particularly susceptible to highly contagious diseases due to their reduced immunity. We studied transplant recipients to gauge their varicella zoster virus (VZV) serology status over time and the outcome of any VZV infections.MethodThis retrospective study comprised 85 children who underwent renal transplants in Gothenburg, Sweden, from 1986 to 2014, at a mean age of eight (1–18) years. The children's medical records were reviewed and 47 had the VZV infection pre‐transplant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…However, both varicella and measles vaccination can be administered as early as six months of age without harm and potential benefit 8 . Studies show that a high number of patients immunized before SOT continue to be seroprotected after SOT and do not require further vaccination 11,14,19,24 . Recently, a study reported 50% of patients (5/10) immunized with MMR before 9 months of age had sustained seroprotection against measles up to 15 years after liver transplantation 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both varicella and measles vaccination can be administered as early as six months of age without harm and potential benefit 8 . Studies show that a high number of patients immunized before SOT continue to be seroprotected after SOT and do not require further vaccination 11,14,19,24 . Recently, a study reported 50% of patients (5/10) immunized with MMR before 9 months of age had sustained seroprotection against measles up to 15 years after liver transplantation 19 .…”
Section: Discussionmentioning
confidence: 99%
“…8 Studies show that a high number of patients immunized before SOT continue to be seroprotected after SOT and do not require further vaccination. 11,14,19,24 Recently, a study reported Briefly, the consensus considered both LAV to be safe in patients who are more than one year after liver or kidney transplantation and more than two months after an acute rejection episode, clinically well, and meet specific criteria of "low-level" immunosuppression.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…Lindahl et al. studied 85 renal transplant patients to see whether they developed varicella zoster virus (VZV) immunity over time. They found that the varicella vaccination provided transplant patients with less protection from symptomatic VZV diseases than natural infections, but it did provide effective protection from life‐threatening diseases.…”
Section: Varicella Vaccination Protects Renal Transplant Patients Fromentioning
confidence: 99%
“…Therefore, the study by Lindahl et al. in this issue of Acta Paediatrica is an interesting contribution to the field, as it provides data on VZV serology over time in children undergoing renal transplants. The authors also evaluated the outcome of any VZV infections post‐transplant.…”
mentioning
confidence: 99%
“…The incidence of the VZV disease after transplant was also evaluated by Lindahl et al. Clinical VZV infections occurred in eight patients during follow‐up, and seven were in the vaccine group. Of these eight children, five were already seronegative at transplantation and the other three became seronegative after surgery, before they developed the VZV.…”
mentioning
confidence: 99%